Central African Economic and Monetary Community (CEMAC) : Staff Report on the Common Policies in Support of Member Countries Reform Programs. (IMF Staff Country Reports; Country Report, 2018)
While improving, CEMAC's economic situation remains fragile. Growth picked up slightly but remains well below potential. Governments' fiscal consolidation efforts, along with BEAC's tighter monetary policy and stricter enforcement of foreign exchange regulations, have contributed to a significant reduction in the region's fiscal and external imbalances. All CEMAC countries are committed to macroeconomic policies agreed with IMF staff to support the economic recovery and financial sustainability of each country and of the region. The regional central bank and banking supervisor continue to implement policies in support of the IMF-supported programs with CEMAC members. However, fiscal slippages in some countries contributed to the underperformance of international reserve accumulation in early 2018. Looking ahead, a further improvement in the economic and financial situation is projected, assuming full implementation of policy commitments by CEMAC member states and regional institutions. This outlook remains subject to substantial risks from possible weaker program implementation, lower oil prices, and insufficient external financing.